Girl helping her family plant strawberries, 1969 - Manuel Echavarria::::::photographer::: (1969)
As a result of low wages, day care was not an option for most farm workers in the Santa Maria Valley. Children also worked to help supplement income for the family. The girl helps her family plant strawberries during May to August season in 1969. Unfortunately, the practice continues to this day.